2010
DOI: 10.1007/s00253-010-2792-z
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol content and expression of phenylalanine ammonia-lyase and stilbene synthase genes in rolC transgenic cell cultures of Vitis amurensis

Abstract: Resveratrol, a naturally occurring polyphenol, has been reported to exhibit a wide range of valuable biological and pharmacological properties. In the present investigation, we show that transformation of Vitis amurensis Rupr. with the oncogene rolC of Agrobacterium rhizogenes increased resveratrol production in the two transformed callus cultures 3.7 and 11.9 times. The rolC-transformed calli were capable of producing 0.099% and 0.144% dry weight of resveratrol. We characterized phenylalanine ammonia-lyase (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 30 publications
1
35
0
2
Order By: Relevance
“…Similar results were reported for Rubia cordifolia cells, in which the rolB gene was more effective than the rolC gene, in the activation of antraquinone biosynthesis (Bulgakov et al 2002). In V. amurensis calli, the rolB gene was also shown to be more effective in the stimulation of resveratrol biosynthesis than the rolC gene, as the rolB gene insertion led to a more than 100-fold increase in resveratrol production, whereas the rolC gene caused a 4-to 12-fold increase in the resveratrol accumulation (Kiselev et al 2007;Dubrovina et al 2010). …”
Section: Productivity Of the Mb1 Mb2 And Mb4 Callus Culturesmentioning
confidence: 99%
“…Similar results were reported for Rubia cordifolia cells, in which the rolB gene was more effective than the rolC gene, in the activation of antraquinone biosynthesis (Bulgakov et al 2002). In V. amurensis calli, the rolB gene was also shown to be more effective in the stimulation of resveratrol biosynthesis than the rolC gene, as the rolB gene insertion led to a more than 100-fold increase in resveratrol production, whereas the rolC gene caused a 4-to 12-fold increase in the resveratrol accumulation (Kiselev et al 2007;Dubrovina et al 2010). …”
Section: Productivity Of the Mb1 Mb2 And Mb4 Callus Culturesmentioning
confidence: 99%
“…Overexpression of the STS genes involved in its biosynthesis can be a promising approach for producing resveratrol. There are consti tutive and inducible forms of STS genes, and their expression is greatly increased with an increasing con tent of resveratrol [14]. It has been suggested previ ously that the enzymatic activity of protein products of constitutive and inducible STS genes may vary [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, when E. coli received the 4CL gene from Lithospermum erythrorhizon and the STS gene from A. hypogea, and coumaroyl-CoA was used as a substrate, resveratrol production reached 171 mg/L (Katsuyama et al 2007). Significant progress in increasing the resveratrol content in plant cells has been achieved by transforming grape cells with the rolC gene of Agrobacterium rhizogenes (Dubrovina et al 2010) and treating the cell cultures with methyljasmonate and cyclodextrins that resulted in a resveratrol content of 1,600 μmol/g (Lijavetzky et al 2008). In the current study, we found that the resveratrol production by Alternaria sp.…”
Section: Discussionmentioning
confidence: 99%